2016
DOI: 10.1126/scitranslmed.aaf1517
|View full text |Cite
|
Sign up to set email alerts
|

The live attenuated dengue vaccine TV003 elicits complete protection against dengue in a human challenge model

Abstract: A dengue human challenge model can be an important tool to identify candidate dengue vaccines that should be further evaluated in large efficacy trials in endemic areas. Dengue is responsible for about 390 million infections annually. Protective efficacy results for the most advanced dengue vaccine candidate (CYD) were disappointing despite its ability to induce neutralizing antibodies against all four dengue virus (DENV) serotypes. TV003 is a live attenuated tetravalent DENV vaccine currently in phase 2 evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
226
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(234 citation statements)
references
References 34 publications
6
226
0
2
Order By: Relevance
“…The lowest serotype-specific response was obtained against DENV2 [53]. To assess the protective efficacy of TV003 towards DENV2, a human challenge model was performed using a DENV2 strain, rDEN2Δ30 [54]. TV003 All four DENV serotypes were produced in insect cells and inactivated with formalin.…”
Section: Live Attenuatedmentioning
confidence: 99%
“…The lowest serotype-specific response was obtained against DENV2 [53]. To assess the protective efficacy of TV003 towards DENV2, a human challenge model was performed using a DENV2 strain, rDEN2Δ30 [54]. TV003 All four DENV serotypes were produced in insect cells and inactivated with formalin.…”
Section: Live Attenuatedmentioning
confidence: 99%
“…Significant progress in vaccine development during the last decade has led to the regulatory authority approval of the first product in 2016 [27]. However, its cost may prevent widespread use in developing countries, [28,29] where control of the mosquito vector will remain the most effective measure to combat dengue [30].…”
Section: Dengue Control Strategiesmentioning
confidence: 99%
“…The DENV1, DENV3, and DENV4 strains used in this vaccine harbor deletions in the 3= untranslated region, and the attenuated strain of DENV4 was employed as a backbone for the remaining dengue virus serotype 2 (15). One formulation (TV003) elicited full protection against DENV infection in small-scale testing using a human challenge model (16). Results of human clinical trials have yet to be reported.…”
Section: Abstract Denv Vaccine Herpesviral Vector Live-vector Vaccimentioning
confidence: 99%